A Comparison of Learning Outcomes in Basic Accounting 2: Recording Goods Transactions in a General Journal with and without VAT Using Problem-Solving versus Conventional Teaching Methods for First-Year Vocational Certificate Students - Pudjaiyo, Nunticha; Pongwiritthon, Kajornatthapol; Thumtheang, Suttipong; Samanpan, Tidarat; Lamanchai, Pichai; Poolpholamnoey, Wadaporn (RATANABUTH JOURNAL, 2024)
Within accounting education, refining pedagogical approaches is vital to improving academic performance. Problem-solving methodologies, widely adopted in mathematics, offer substantial enhancements to critical thinking, decision-making, and analytical abilities. This study examines learning outcomes in accounting courses by comparing problem-solving techniques with traditional teaching methods, aiming to better prepare students for future professional challenges. This research aimed to 1) To compare the learning achievement in Basic Accounting 2: Recording Sales Transactions in General Journals, with and without Value Added Tax, among first year Higher Vocational Certificate students before and after instruction using the problem-solving teaching method. 2) To compare the learning achievement in Basic Accounting 2: Recording Sales Transactions in General Journals, with and without Value Added Tax, among first year Higher Vocational Certificate students before and after instruction using the traditional teaching method. 3) To compare the learning achievement in Basic Accounting 2: Recording Sales Transactions in General Journals, with and without Value Added Tax, among first year Higher Vocational Certificate students taught using the problem-solving teaching method versus the traditional teaching method. 4) To compare the satisfaction of first year Higher Vocational Certificate students with the learning experience in Basic Accounting 2: Recording Sales Transactions in General Journals, with and without Value Added Tax. The sample consisted of 60 first year Higher Vocational Certificate students in Room 2 of the Digital Marketing Program, Semester 1, Academic Year 2024 at Thai-Asia Technology College, selected through two-stage random sampling. Two classrooms were randomly selected and subsequently assigned as the experimental group and the control group, each comprising 30 students. The research instruments included 1) a learning management plan employing the problem-solving teaching method, 2) a learning management plan employing the conventional teaching method, 3) an academic achievement test with a reliability coefficient of 0.846, and 4) a learning satisfaction questionnaire. The data were analyzed using mean, standard deviation, and t-test statistics. The findings revealed that 1) academic achievement in both the problem-solving and conventional teaching methods improved significantly after instruction, at the 0.05 significance level 2) academic achievement was significantly higher with the problem-solving method compared to the conventional method, at the 0.05 significance level and 3) student satisfaction was significantly higher with the problem-solving method than with the conventional method, at the 0.05 significance level.